2014
DOI: 10.1166/jnn.2014.9353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coupling Protocols to Bind Beta-Glucosidase on Magnetic Nanoparticles

Abstract: Beta-Glucosidase has been chosen as a model biomolecule to establish a general protocol for binding enzymes on both ferromagnetic and superparamagnetic nano-particles for sensing applications. Using EDC (1-(3-dimethyl-aminopropyl)-3-ethylcarbodiimide) or SMCC (Succinimidyl-4-(N-maleimidomethyl)cyclohexane-1-carboxylate) as coupling agents, we compared two different methods for the fabrication of enzyme-decorated magnetic nanoparticles. We identified the best conditions for the preparation of a responsive bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…More specifically, the highest immobilization efficiency was observed for bgl on iron-based nanomaterials, rather than on functionalized GO. Similar immobilization efficiencies have been previously reported for bgl on magnetic nanoparticles (Ricco et al, 2014) or GO-iron nanoparticles hybrid nanomaterials (Gokhale et al, 2013;Ricco et al, 2014). It is interesting to note that the type of amine groups on the surface of the hybrid nanomaterial seems to affect the immobilization efficiency.…”
Section: Immobilization Yield and Activity Of Immobilized Bglsupporting
confidence: 83%
“…More specifically, the highest immobilization efficiency was observed for bgl on iron-based nanomaterials, rather than on functionalized GO. Similar immobilization efficiencies have been previously reported for bgl on magnetic nanoparticles (Ricco et al, 2014) or GO-iron nanoparticles hybrid nanomaterials (Gokhale et al, 2013;Ricco et al, 2014). It is interesting to note that the type of amine groups on the surface of the hybrid nanomaterial seems to affect the immobilization efficiency.…”
Section: Immobilization Yield and Activity Of Immobilized Bglsupporting
confidence: 83%
“…β-Glu has been successfully immobilized on magnetic nanoparticles and showed favourable activity. 37,38 In a previous study, we also prepared β-Glu-loaded magnetic nanoparticles and confirmed their targeted delivery using a mouse model of subcutaneous 9L glioma. 39 Moreover, polyethylene glycol (PEG) modification of β-Glu increased the in vivo stability of MNP-β-Glu and enhanced their accumulation in the targeted tumor tissue.…”
Section: Introductionmentioning
confidence: 59%